Implementation of a model of a metainformation-controlled editor of information units with a complex structure - Gribova, V. V.; Kleshchev, A. S.; Moskalenko, F. M.; Timchenko, V. A. (Automatic documentation and mathematical linguistics, 2016)
This paper describes the model and methods for implementing an extensible tool for editing information with a complex structure with different levels of abstraction and invariance to technological spaces (subject domains) in a common conceptual framework for carriers of this information; this makes it unnecessary to arrange specialized training for these carriers or involve professional intermediaries.